WORK STRESS AND WORK MOTIVATION IN RELATION TO PERCEIVED WORK PRODUCTIVITY AMONG INPATIENT NURSES - Idham Latif; Muhamad Fauzi; Saltsabilla Rahmani Putri (Universitas Kusuma Husada Surakarta, 2026)
Background: Improving nurses’ work productivity is essential to ensure high-quality hospital services, yet labor productivity in Indonesia remains relatively low, highlighting the need to identify factors that influence nurses’ performance. This study aimed to analyze the relationships among work stress, work motivation, and perceived work productivity among inpatient nurses. This study aimed to analyze the relationships among the independent variables (work stress and work motivation) and the dependent variable (perceived work productivity) among inpatient nurses. Methods: A quantitative, cross-sectional design was employed, involving a population of 190 nurses and a sample of 130 respondents selected via accidental sampling. Before data collection began, the questionnaire was tested for validity and reliability. Multiple logistic regression and chi-square tests were used to analyze the data.Results: Most nurses reported low levels of work stress, high motivation, and high perceptions of their own productivity. Statistical analysis revealed a significant relationship between work stress, work motivation, and perceived work productivity (p < 0.05). Furthermore, work motivation was identified as the most dominant factor influencing perceived work productivity, with an odds ratio of 6.999.Conclusion: Both work stress and work motivation are significantly associated with nurses’ perceived work productivity, with motivation emerging as the most dominant factor. Hospital management should prioritize strategies that strengthen intrinsic work motivation and implement adaptive work stress management programs to sustain optimal perceived productivity and performance.